Effects of Mycoestrogens on Female Reproduction - Christian Lee Andersen (Reproductive and Developmental Medicine, 2018)
Zearalenone (ZEA) is produced by Fusarium species and a common contaminant in food. ZEA and its metabolites, α- and β-zearalenol, α- and β-zearalanol, and zearalanone, are mycoestrogens that can interfere with estrogen signaling. High levels of mycoestrogens reduced female fertility in farm animals and rodents, in which adverse effects of mycoestrogens on major events in female reproduction, including ovarian folliculogenesis, ovulation, ovarian steroidogenesis, fertilization, preimplantation embryo development and transport, embryo implantation, placentation, parturition, and lactation, have been reported in different experimental settings. Here, we review the in vivo effects of mycoestrogens on the main events in female reproduction.